2022
DOI: 10.3390/agriculture12111955
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Long-Term Fertilization System Use on Physical and Microbiological Soil Status in the Western Polissia of Ukraine

Abstract: The response of soil microbial diversity to long-term fertilization is still not well understood in the context of different soil types. The purpose of this research was to reveal the impact of fertilization systems on soil parameters and life activity of the main taxonomic and physiological groups of microorganisms responsible for nitrogen, carbon, and phosphorus transformation. Reported results were obtained in the course of a 55-year-long experiment on fertilization of sod-podzolic soil in a grain-flax-pota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 78 publications
0
4
0
1
Order By: Relevance
“…This finding supports previous observations that protistan communities are more sensitive to organic fertilizer inputs than other microbial groups (e.g., bacteria and fungi) in diverse agricultural soils 21,22 , potentially explained by the highly diverse taxonomic, trait and functional diversity of protists that together surpasses that of other microbial groups 15,24 . In addition, numerous previous studies demonstrated that long-term different organic fertilization changes the soil physicochemical environment 25,26 . A stronger response of protistan communities to bioorganic fertilization than of bacterial and fungal communities suggests that protists are more strongly changed, potentially explained by their larger taxonomic, trait and functional diversity might make them more responsive to changes in the surrounding physicochemical environment as induced by bioorganic fertilizer inputs 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports previous observations that protistan communities are more sensitive to organic fertilizer inputs than other microbial groups (e.g., bacteria and fungi) in diverse agricultural soils 21,22 , potentially explained by the highly diverse taxonomic, trait and functional diversity of protists that together surpasses that of other microbial groups 15,24 . In addition, numerous previous studies demonstrated that long-term different organic fertilization changes the soil physicochemical environment 25,26 . A stronger response of protistan communities to bioorganic fertilization than of bacterial and fungal communities suggests that protists are more strongly changed, potentially explained by their larger taxonomic, trait and functional diversity might make them more responsive to changes in the surrounding physicochemical environment as induced by bioorganic fertilizer inputs 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Soil is the main medium for plant growth, germination, and development, and fertilization helps both plants and microorganisms to grow in the soil environment. However, the increase in the use of fertilizers on farm fields over the past 50 years has contributed to increased yields but also caused serious environmental problems [1][2][3][4][5]. Consequently, one of the main goals of the European Commission's "Farm to Folk" strategy, which was recently adopted to ensure a sustainable food value chain, is to reduce fertilizer use by at least 20% by 2030.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, understanding and assessing the impact of reduced fertilizer application rates on soil fertility are not possible without recognizing the most important chemical characteristics of soils (e.g., pH, carbon, and nutrient element content). The pH of agriculturally exploited soils is generally acidic, limiting the uptake of nutrients, which are converted into a form inaccessible to plant roots and microorganisms [4,5,20,21]. This usually results in a decrease in yields [9,14].…”
Section: Introductionmentioning
confidence: 99%
“…La aplicación adecuada de fertilizantes nitrogenados promueve el macollamiento, el crecimiento, el metabolismo del nitrógeno, la distribución de la materia seca y la acumulación de azúcar y, por lo tanto, mejora significativamente la productividad de caña y azúcar. En este contexto, el uso a largo plazo de diferentes sistemas de fertilización puede generar disímiles condiciones sobre la actividad vital de los principales grupos taxonómicos y fisiológicos de los microorganismos del suelo (Puzniak et al 2022), sin que existan evidencias sobre este particular para agroecosistemas tropicales insulares.…”
Section: Introductionunclassified